Civil ways to protect innovation in startups as in business projects - O.V. Belaya; Yu.A. Kitsay (Ученые записки Казанского университета: Серия Гуманитарные науки)
This paper raises questions about the definition of the concept and essence of startups. Three main approaches to understanding the essence of startups were considered: as a legal entity, as a project, and as a company or project. It was noted that startup projects are very similar in their nature to innovation projects. Startup projects are protected exclusively from the perspective of intellectual property. In this case, at least two objects of intellectual property emerge – a project, i.e., an action plan complying with a certain objective form, which relates to copyright objects, in the form of another work; as well as the innovation itself, which, depending on its essence, can be either embodied in the object of copyright and patent law or belongs to the objects of non-traditional protection (selection achievements, topologies, know-how). A startup project is a combination of these two intellectual property objects. In this regard, it can be attributed to complex objects, which combine several results of intellectual activity. The obtained results suggest that members of a startup project team must enter into a contractual relationship with each other. The conditions of such contracts were analyzed.